Islamic Education Learning Based on Experiential Learning in Forming Morals Students in the Digital Era at SMKN 1 Kota Bima - Khaeratunisa; Sri Jamilah; Kaharuddin (Lembaga Bale Literasi, 2025)
The development of the digital era brings challenge for formation morals vocational school students, especially in ethics media social research This aim explore implementation Islamic Religious Education learning based on experiential learning in form morals students at SMKN 1 Bima City. Research use method qualitative with design studies case. Data collected through observation, interviews, questionnaires, and documentation. Research results show implementation done through three activities main: project campaign digital ethics, simulation sell buy online syar'i, and journals digital reflection. Change morals student seen in the increase awareness digital ethics, improving communication etiquette in group class, and the emergence initiative make content positive. Supporting factors covering relevance method with character vocational school students and the role of teachers as facilitator. Inhibiting factors is limitations time learning and inequality internet access. Research concludes that experiential learning effective for learning morals in the digital era because connect experience real student with Islamic values through a meaningful reflection process.